PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA MINAT BELI ULANG (Studi Pada Konsumen Restoran Pizza Hut di Kota Pontianak) - admin, QISTHINA YOLANDA B11112090 (Jurnal Manajemen Update, 2016)
This study aimed to determine the influence of experiential marketing on customer satisfaction and the effect on repurchase intention in Pizza Hut Restaurant Pontianak. This research consists of independent variables which are experiential marketing consists of sense, feel, think, actÂ  and relate, intervening variable which is customer satisfaction, and dependent variable which is repurchase intention. The method used in this study is survey, while the technique of data collection is done through the questionnaire. The population in this research is the customer of Pizza Hut Restaurant Pontianak, with sample of 100 respondents. The sampling technique is use purposive sampling and then the data analyzed by path analysis. The results of analysis for the first model show partially that feel, think, and relate have a significant effect on customer satisfaction. Then sense and act have no significant effect on customer satisfaction. Predictive capability of the five variabels on customers satisfaction is 39,1% while the remaining 60,9% was influenced by other factors out of this research model. The results of analysis for the second model show partially that customer satisfaction have a significant effect on repurchase intention. Predictive capability of this variabels on repurchase intention is 32,3% while the remaining 67,7% was influenced by other factors out of this research model. Keywords: sense, feel, think, act, relate, customer satisfaction and repurchase intention Â